Microwave assisted pyrolysis of Kraft lignin in single mode high-Q resonant cavities: Degradation kinetics, product chemical composition, and numerical modeling. (15th February 2021) - Nde, Divine B.; Muley, Pranjali D.; Sabliov, Cristina M.; Nokes, Sue E.; Boldor, Dorin
Highlights: Mass loss kinetics of kraft lignin is established in a single mode high-Q resonant cavity. Activation energies and pre-exponential factors indicate that energy requirements are low. Numerical modeling of the heating process demonstrates significant effect of sample position. Major pyrolysis products include phenols and phenolics. Abstract: Useful fuels and chemicals can be produced from lignin by microwave-assisted pyrolysis, but a dearth of understanding of this process impedes its successful implementation. Continuous mass loss kinetics of the pyrolysis of Kraft lignin pellets were carried out in an innovative reactor system comprised of a high-Q cylindrical microwave resonant cavity and a specially designed quartz reactor, in the temperature range of 300–700 °C. Multiphysics numerical simulations indicated that both absorbed power and resulting temperatures profiles are heavily dependent on position of the sample relative to the electric field. Kraft lignin degradation (5 g samples) was complete in about 40 s, which was much faster than conventionally heated reactors. Activation energies (5–22 kJ/mol) and pre-exponential factors (0.06–0.64 s −1 ) were indicative that the process is low in energy consumption. At higher temperatures, phenols and phenolics were the major constituents of the bio-oil. A reliable method of obtaining microwave-assisted mass loss kinetics continuously is established.